The most common illnesses caused by office work - Tatara, Tomasz; Dąbrowska-Bender, Marta (Polish Journal of Public Health, 2010)
Professional work is an important element of human existence, absorbing more than half of life. Office work is the most popular and desirable in many societies, because it is associated with minimal physical effort, simplicity and comfort. Although light because of its sedentary nature and low energy expenditure, office work is also considered onerous, including the persistence of the forced body position. Long-term performance of service in the office is more and more often causes the occurrence of various problems of the musculoskeletal and cardiovascular systems and sight. This situation is connected not only with the nature of work, but also the working conditions and behaviour of individual employees. An effective way to prevent these illnesses is to implement the principles of ergonomics that optimize the working conditions and minimize their negative impact on health.In this work the most important health affecting factors have been presented and the most common diseases associated with long-term performance of office work (and suggested treatment of them) have been described. In addition, widely understood prophylaxis against ‘office’ diseases has been shown – from the importance of health promotion in the workplace offered by the employer to the role of properly designed ergonomic workstation.